USE OF ORIGAMI PAPER IN MATHEMATICS LEARNING FOR ELEMENTARY SCHOOL CHILDREN IN BLANG MIRO VILLAGE - Anzora Anzora; Linda Fajri; Marda Yanti; Aria Zulfahmi (Universitas Muhammadiyah Aceh, 2022)
Blang miro village is one of the villages in Aceh Besar which is located in the mountains, where the residents are farmers and gardeners. From the results of surveys and interviews with residents, it was found that there are still many children in elementary schools in the village who are less interested in learning mathematics, because they are considered the subject to be difficult and less interesting. So that the value for math lessons decreased. So the purpose of this service is to teach mathematics by using simple teaching aids for elementary school children, so that interest in learning mathematics arises. One of them is to use origami paper on fractional material and build a flat or wake up space. The method used is contextual learning, simulation and testing of teaching aids. The results of this service are 1) participants can make simple teaching aids 2) participants can use teaching aids in learning mathematics, especially fractions and flat shapes or shapes 3) participants enjoy using teaching aids and increase student interest in learning mathematics.Keywords: mathematics, origami paper